International standards on the rights of convicted persons in places of imprisonment - Підгородинський, Вадим Миколайович; Підгородинський, В. М.; Подгородинский, Вадим Николаевич; Pidhorodynskyi, Vadym M.; Pidgorodynskyi, Vadym; Тихоненко, Вадим Миколайович; Тихоненко, В. М.; Тихоненко, Вадим Николаевич; Tykhonenko, Vadym M.; Цехан, Дмитро Миколайович; Цехан, Д. М.; Цехан, Дмитрий Николаевич; et al. (University of Zulia, 2021)
The relationship between crime and punishment has never been isolated. Under the influence of socio-economic, political, and cultural changes, metamorphoses of the institution of execution of punishments took place; in particular, the rights of convicts were liberalized. Therefore, it is necessary to analyze the historiography of this phenomenon in terms of international standards, as well as the peculiarities of their implementation. The work aims to characterize the implementation of international standards on the rights of prisoners in terms of historiography and legal regulation. The object of research is the norms of international law. The subject of the study is social relations that arise in the implementation of international standards on the rights of convicts in prisons. The research methods were dialectical, systemic, structural, formal-legal, historical-legal, methods of analysis, synthesis, induction, and deduction. As a result, international standards for the rights of prisoners serve as a model, an example of rational social relations in the penitentiary environment. Key aspects that should be universally taken into account by the governments of all countries are identified and described.

Зв'язок між злочином і покаранням ніколи не був ізольованим. Під впливом соціально-економічних, політичних і культурних змін відбулися метаморфози інституту виконання покарань; зокрема лібералізувалися права засуджених. Тому необхідно проаналізувати історіографію цього явища з точки зору міжнародних стандартів, а також особливостей їх реалізації. Робота має на меті охарактеризувати впровадження міжнародних стандартів щодо прав ув’язнених з точки зору історіографії та правового регулювання. Об'єктом дослідження є норми міжнародного права. Предметом дослідження є суспільні відносини, що виникають при реалізації міжнародних стандартів щодо прав засуджених у місцях позбавлення волі. Методами дослідження були діалектичний, системний, структурний, формально-правовий, історико-правовий, методи аналізу, синтезу, індукції та дедукції. Як наслідок, міжнародні стандарти щодо прав ув’язнених служать зразком, прикладом раціональних соціальних відносин у пенітенціарному середовищі. Визначено та описано ключові аспекти, які мають брати до уваги уряди всіх країн.
Pidgorodynskyi V. International standards on the rights of convicted persons in places of imprisonment / V. Pidgorodynskyi, V. Tykhonenko, D. Tsekhan, P. Kaminskyi, S. Kravchenko // Cuestiones Políticas. - Vol. 39. - Issue 68. - University of Zulia, 2021. - P. 121-135.
Keywords: prisoner's rights; international law; international standards on prisoner's rights; criminal-executive law; penitentiary system; права ув'язнених; міжнародне право; міжнародні стандарти з прав ув'язнених; кримінально-виконавче право; пенітенціарна система; Research Subject Categories::LAW/JURISPRUDENCE